ANALlSlS KOMPOSlSl DAN STRUKTUR VEGETASI DI KAWASAN TAMAN WlSATA ALAM PULAU BAKUT KECAMATAN ANJlR MUARA KABUPATEN BARlTO KUALA KALlMANTAN SELATAN - Nor Aida Azizah; Abdi Fithria; Gusti Syeransyah Rudy; Rina Kanti; Hafif Abdul Rahman; Riyanto Imam (Jurnal Sylva Scienteae, 2024)
Indonesia is an example of a country with the largest type of mangrove forest ecosystem and has abundant wealth. One of the forests with this type of mangrove ecosystem in South Kalimantan is in the Bakut Island Natural Tourism Park area. The Bakut Island TWA itself is a residential place for a typical Kalimantan primate, namely the Proboscis Monkey (Nasalis Larvatus). Knowing information about ecological aspects related to the structure (shape) and composition (arrangement) of vegetation in this area is the first step in managing and preserving mangrove forest areas. In this research process the researchers intended to anaIyze the structure and composition of the mangrove forest vegetation types and calculate the species diversity index in the Bakut Island Nature Park area. Data was collected using a combination method, namely a combination method between the path method and the checkered Iine method which was carried out intentionally (purposive sampling). The data were then analyzed in several calculations to find the lmportance VaIue lndex and Species Diversity lndex. In the results of this study there were 22 plant species divided at several growth stages, namely seedlings, saplings, poles and trees. As for the diversity index of the types of values obtained at all levels of growth, it is included in the low diversity categoryIndonesia adalah satu contoh negara dengan tipe ekosistem hutan mangrove terbesar serta memiliki kekayaan yang melimpah.  Salah satu hutan dengan tipe ekosistem mangrove di Kalimantan Selatan ada di kawasan Taman Wisata Alam Pulau Bakut. TWA pulau bakut sendiri merupakan tempat hunian bagi satwa primata khas Kalimantan yaitu Bekantan (Nasalis Larvatus). Mengetahui informasi mengenai aspek ekologis terkait struktur (bentuk) dan komposisi (susunan) vegetasi yang ada di kawasan ini merupakan langkah awal dalam melakukan pengelolaan dan pelestarian kawasan hutan mangrove. Pada proses penelitian ini peneliti bermaksud untuk menganalisis struktur serta komposisi jenis vegetasi hutan mangrove dan menghitung indeks keragaman jenis di kawasan Taman Wisata Alam Pulau Bakut. Data diambil dengan metode kombinasi yaitu metode gabungan antara metode jaIur dan metode garis berpetak yang dilakukan secara sengaja (purposive sampling). Data kemudian dianalisis pada beberapa perhitungan untuk mencari lndeks NiIai Penting dan lndeks Keanekaragaman Jenis.  Pada hasiI peneIitian ini terdapat 22 jenis tumbuhan yang terbagi pada beberapa tingkat tunbuh yaitu semai, pancang, tiang dan pohon. Sedangkan untuk lndeks Keragaman jenis nilai yang di dapat pada semua tingkat pertumbuhan termasuk dalam kategori keanekaragaman rendah.